Land Ecosystem Service Functions for Dongting Lake Ecological Economic Zone Based on InVEST Model - Yang Jun; Zhou Pengquan; Yuan Shujun; Tan Xin; Lou Zhifei (Shuitu baochi tongbao)
[Objective] The spatial distribution of ecosystem services for Dongting Lake was studied to improve the ecosystem services in the study area and in the Yangtze River Basin, and provide a reference for soil conservation, land use, and ecological protection. [Methods] The tradeoff relationship between the quality of four ecosystem services and the four ecosystem service functions of water conservation, soil conservation, carbon storage, and habitat quality in 2005 and 2018 was evaluated for the Dongting Lake Ecological Economic Zone using the InVEST model. [Results] ① Land use conversion was mainly based on conversion between forest land and cultivated land, water area and cultivated land, and conversion of forest land and cultivated land into construction land. ② The water source conservation and soil conservation functions were significantly improved, and the carbon storage and habitat quality functions were slightly reduced. ③ The low-value areas of water conservation, carbon storage, habitat quality, and functional substance quality were located near the central lake area of the study area, while the high-value areas of soil conservation functional material quality were mainly located in the east, southwest, and northwest. [Conclusion] Land use and the quality of ecosystem services in the Dongting Lake ecological economic zone changed greatly during the study period as the area was affected by the objective needs of economic development and relevant ecological protection policies (such as returning farmland to lakes and returning farmland to forests). There is a tradeoff relationship between water conservation and habitat quality in the study area, a compatible relationship between water conservation and soil conservation, and a synergistic relationship among other ecosystem services. The InVEST model provides a more comprehensive assessment of ecosystem service functions.